Development of Information Literacy from the Period of Rasulullah to Khulafaur Rasyidin - Merdekawati, Nur Rahmah; Syam, Kadri Ariski; Mathar, Muh. Quraisy (Universitas Airlangga, 2025)
Background of the study: Islamic civilization underwent a significant transformation from an oral tradition society to a literate culture during the time of the Prophet Muhammad and the period of the Khulafaur Rasyidin. This transition represents a crucial development in information literacy that fundamentally shaped Islamic educational and scientific traditions, but comprehensive analysis of this historical evolution remains limited. Purpose: This study aims to examine the development of information literacy from the time of the Prophet Muhammad until the period of the Khulafaur Rasyidin, analyzing how Islamic civilization evolved from an oral tradition into a comprehensive literacy culture that values reading, writing, and the systematic dissemination of knowledge. Methods: The researcher uses qualitative literature research methodology, conducting a systematic analysis of historical sources and Islamic literature to understand the evolution of literacy practices and educational institutions in the early period of Islam. Finding: Re Research indicates that the initial revelation,